The Hunting of the Snark : an Agony in Eight Fits. - Carroll, Lewis, 1832-1898 (Floating Press, 1876)
The Hunting of the Snark (An Agony in 8 Fits) is a nonsense poem written by Lewis Carroll (Charles Lutwidge Dodgson) in 1874, when he was 42 years old. It describes "with infinite humor the impossible voyage of an improbable crew to find an inconceivable creature". The poem borrows occasionally from Carroll's short poem Jabberwocky in Through the Looking-Glass (especially the poem's creatures and portmanteau words), but it is a stand-alone work, first published in 1876 by Macmillan ...